Microvascular Complications in Cystic Fibrosis-Related Diabetes Mellitus: a Case Report. - Scott, Andrew IR; Clarke, Belinda E; Healy, Helen; D'Emden, Michael; Bell, Scott C (JOP. Journal of the Pancreas, 2016)
Context The prevalence of cystic fibrosis-related diabetes mellitus is increasing and is associated with increased survival from cystic fibrosis. Case Report This study describes a case of the premature onset of disabling and widespread microvascular complications resulting from cystic fibrosis-related diabetes mellitus. Previously asymptomatic retinopathy was diagnosed on recognition of diabetic nephropathy. Conclusions The treatment of pulmonary exacerbations has become more complex due to the nephrotoxic potential of intravenous aminoglycoside drugs which are frequently used to control chronic Pseudomonas infection in cystic fibrosis. Image: Renal biopsy: glomeruli with a global increase in the mesangial matrix.